Transformasi Wanita Karir Perspektif Gender Dalam Hukum Islam (Tuntutan Dan Tantangan Pada Era Modern) - Sunuwati Sunuwati; Rahmawati Rahmawati (An Nisa'a, 2017)
Gender questioned for giving birth to the different roles, responsibilities, rights and functions as well as space activities between men and women in society. That difference makes people tend to be discriminatory access, participation and control in the results of development and career development between men and women. Gender equality cause no difference in the rights and obligations between men and women in the employment sector. But what about the Islamic view of equality of rights and obligations, are there any limitations for women in the work given their nature as women.